1991
DOI: 10.1111/j.1467-7717.1991.tb00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Shelter, Housing and Recovery: A Comparison of U.S. Disasters

Abstract: In this paper we examine the issues associated with the temporary sheltering and housing of victims after natural disasters in the United States. Specific topics addressed include differential access to shelter and housing aid according to social class, ethnicity and related demographic factors; the relationship between post-disaster shelter and housing and long-term recovery; the role of social support networks in the sheltering of victims; and the implications of the research for the provision of shelter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 6 publications
0
81
1
2
Order By: Relevance
“…Mobile homes are particularly susceptible to damage from high winds and are generally less resilient in disasters than standard housing (Bolin and Stanford 1991;Chakraborty et al 2005;Cutter et al 2000;Heinz Center 2000). These structures, therefore, warrant special attention.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Mobile homes are particularly susceptible to damage from high winds and are generally less resilient in disasters than standard housing (Bolin and Stanford 1991;Chakraborty et al 2005;Cutter et al 2000;Heinz Center 2000). These structures, therefore, warrant special attention.…”
Section: Background Literaturementioning
confidence: 99%
“…In this context, mobile home residents located in high-risk coastal areas are distinctly vulnerable populations because of the limited protection afforded by their dwellings and their socio-economic status. Research has shown, for instance, that age, gender, household size, education, income, health, pet ownership, and structural conditions of homes all influence disaster outcomes (e.g., Bolin and Stanford 1991;Cutter and Finch 2008;Enarson and Scanlon 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This perspective highlights the social construction of vulnerability. A wide variety of variables are examined as indicators of such social vulnerability, including gender (Enarson & Morrow 1998), age (Bolin & Klenow 1983), disability (Parr 1987), family structure and social networks (Drabek & Key 1986), housing and built environment (Bolin & Stanford 1991, Quarantelli 1991, income and material resources (Bolin & Stanford 1991), and race and ethnicity (Bolin & Bolton 1986, Fothergill et al 1999. As pointed out by Cutter (1996), although the vulnerability indicators are often single variables, they are manifestations of multidimensional factors such as institutional development, social relations, or political power.…”
Section: Meanings Of Vulnerabilitymentioning
confidence: 99%
“…Additionally, various stakeholders such as not only landowners but also renters and merchants were involved in community management before the EJET, however, opinions from such stakeholders except land owners are not reflected on community recovery if target to participate in the consultation limits only landowners. Involving local citizen groups in coalition with government and private disaster organizations will improve the effectiveness of a program (Bolin and Stanford 1991). It is needed to make reconstructed community resilient by involvement of multi-stakeholders at the stage of making community recovery plan and by being conducted as actors or supporters of the plan.…”
Section: Resilience Building In the Recovery Process By Involvement Omentioning
confidence: 99%